2023
DOI: 10.21203/rs.3.rs-2488586/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical testing of transcriptome-wide expression profiles in high-risk localized and metastatic prostate cancer starting androgen deprivation therapy: an ancillary study of the STAMPEDE abiraterone Phase 3 trial

Abstract: Metastatic and high-risk localized prostate cancer respond to hormone therapy but outcomes vary. Following a pre-specified statistical plan, we used Cox models adjusted for clinical variables to test associations with survival of multi-gene expression-based classifiers from 781 patients randomized to androgen deprivation with or without abiraterone in the STAMPEDE trial. Decipher score was strongly prognostic (p<2x10-5) and identified clinically-relevant differences in absolute benefit, especially for local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In that study, investigators found that tumors with increased interferon alpha (and other tumor immune related signatures) were associated with increased presence of tumor infiltrating lymphocytes by immunohistochemical analysis and had worse outcomes with radiation and hormonal therapy. 20 Our study has several limitations that warrant discussion. The small sample size and short median follow-up of 2 years has limited our power to detect differences and precluded our ability to use a proven surrogate endpoint for survival, such as metastasis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In that study, investigators found that tumors with increased interferon alpha (and other tumor immune related signatures) were associated with increased presence of tumor infiltrating lymphocytes by immunohistochemical analysis and had worse outcomes with radiation and hormonal therapy. 20 Our study has several limitations that warrant discussion. The small sample size and short median follow-up of 2 years has limited our power to detect differences and precluded our ability to use a proven surrogate endpoint for survival, such as metastasis.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, our observation that tumor immune signatures were correlated with the absolute number of TLS is similar to the recent findings from an ancillary analysis of the STAMPEDE trial. In that study, investigators found that tumors with increased interferon alpha (and other tumor immune related signatures) were associated with increased presence of tumor infiltrating lymphocytes by immunohistochemical analysis and had worse outcomes with radiation and hormonal therapy 20 …”
Section: Discussionmentioning
confidence: 98%
“…We found increased expression of PIA gene markers 66 KRT5, KRT8, and MET, and PIA-associated club-like cell gene markers 17,24 9 . Inflammation-associated low-CD38 expressing luminal cells have previously been associated with biochemical recurrence 68 , whereas high IFNγ signaling is associated with worse outcomes in high-risk localized disease 69 . These results indicate that the club-like cells are interchangeably linked with inflammation in the prostate TME.…”
Section: Discussionmentioning
confidence: 99%
“…Similar inflammatory signaling activity has been reported in club-like cells of histologically benign glands proximal to invasive cribriform carcinoma or intraductal carcinoma-enriched regions 9 . Inflammation-associated low-CD38 expressing luminal cells have previously been associated with biochemical recurrence 68 , whereas high IFNγ signaling is associated with worse outcomes in high-risk localized disease 69 . These results indicate that the club-like cells are interchangeably linked with inflammation in the prostate TME.…”
Section: Discussionmentioning
confidence: 99%
“…A robust evidence review was therefore performed, and a level of evidence based on Simon criteria 22 was determined for various risk stratification models (see PROS-H page 2 of 8 in the full version of these guidelines, available at NCCN.org) and advanced risk stratification tools (see Figure 1). Literature published on the 22-gene genomic classifier assay (Decipher), [23][24][25][26][27][28] the 31 cell cycle progression gene assay (Prolaris), [29][30][31] the 17-gene assay Genomic Prostate Score assay (GPS), 32 and the multimodal artificial intelligence model (ArteraAI Prostate) 33,34 in both the initial treatment and the post-radical prostatectomy (RP) settings were reviewed.…”
Section: Advanced Risk Stratification Toolsmentioning
confidence: 99%